EVALUATION OF PHYSIOLOGICAL GROWTH PARAMETERS OF MAIZE IN MAIZE-LEGUME INTERCROPPING SYSTEM - I. Yavas; A. Unay (Journal of Animal and Plant Sciences, 2016)
Field trial was conducted in 2011/2012 and 2012/2013 to determine the maize growth parameters under maize-soybean and maize-cowpea intercropping system at different reproductive stages. The varieties used were Umut 2002 (soybean), Karagoz (cowpea) and PR31G98 (maize) while the cropping treatments were sole and intercrop (alternate-rows). The experimental design was a randomized complete block design with three replicates. Results showed that maize planted (alternate-rows) simultaneously with cowpea and soybean recorded significantly higher values of leaf area index (LAI), leaf area ratio (LAR) and net assimilation rate (NAR). Highest values of NAR was recorded at R1 stage; LAI, LAR and relative growth rate (RGR) through at vegetative growth stage. LAI (sole maize) and NAR (1M+1C) showed significant correlation with grain yield. LAR and RGR for maize decreased from VT to R6. The LAI and NAR at silking stage have been identified as the major determinants of grain yield.
Keywords: Alternate intercropping; cowpea; LAI; RGR; soybean